Racismo@online.com.br : as relações raciais a partir da análise de blogs - Assis, Marcelo Francisco de (2011)
Internet is today a tangible reality to a great part of the Brazilian population. Those places work like mechanisms capable of engendering new areas of social exchange. This paper proposes to analyze racism in Maringá, Paraná State, by interpreting the speeches posted in three blogs from people who live in this same city. Inasmuch as this way to share information is related to cyberculture, we understand that its production as a social action. Upon a Social Sciences based-methodology, however particularly on Interpretivism, we deconstructed the net surfers' discussions registered in this field, connecting its conception regarding to racial relations in the researched city to the conception on racial discrimination produced in Brazil and shared by its citizens. The interpreted posts have shown us the rhetorical reproduction, which content is racist, structured by discussions that uphold the maintenance of the present status quo, where any affirmative political approach is interpreted as a paternalist action. The use of the term race is always considered in order to distinguish the social agents, as well as the racial myth is used as a way to deny that there are racial manifestations in our society as a whole.